2021
DOI: 10.1096/fj.202002558rr
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular matrix proteins type I collagen, type III collagen, fibronectin, and laminin 421 stimulate migration of cancer cells

Abstract: For metastasis formation, individual cells from a primary tumor must migrate toward other tissues. The aim of this study was to determine if mesenchymal stromal cells (MSCs) from human bone marrow are able to emit signals that induce this migratory activity in cancer cells. We separated the supernatant of MSCs derived from human bone marrow by size‐exclusion and ion‐exchange chromatography and have subsequently studied the migratory behavior of the prostate cancer cell line PC3 and the breast cancer cell line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 58 publications
(98 reference statements)
2
18
0
Order By: Relevance
“…The appearance of the BM results in loss in cell movement; compaction and stabilization of intercellular relationships and formation of lumen. In fact, down-regulation of fibronectin-1 in blastuloid spheroids, is consistent with its well-established role in driving migration of cancer cells (Graf et al, 2021). Moreover, fibronectin is a well-known mesenchymal marker, and its down-regulation in blastuloid spheroids, along with establishment of lumen, polarity, and a BM-like ECM coat implies a consonance between moruloid-to-blastuloid and mesenchymal to epithelial transition.…”
Section: Discussionsupporting
confidence: 75%
“…The appearance of the BM results in loss in cell movement; compaction and stabilization of intercellular relationships and formation of lumen. In fact, down-regulation of fibronectin-1 in blastuloid spheroids, is consistent with its well-established role in driving migration of cancer cells (Graf et al, 2021). Moreover, fibronectin is a well-known mesenchymal marker, and its down-regulation in blastuloid spheroids, along with establishment of lumen, polarity, and a BM-like ECM coat implies a consonance between moruloid-to-blastuloid and mesenchymal to epithelial transition.…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, several molecular signals reported to promote the establishment of metastatic foci in the bones are expressed during somitogenesis. This holds true for the chemokine CXCL12/SDF-1, WNTS, and HGF, as well as extracellular matrix proteins such as tenascins and fibronectins ( Clézardin et al., 2021 ; Graf et al., 2021 ; Kar et al., 2020 ; Previdi et al., 2010 ; Scaal et al., 1999 ; Stebler et al., 2004 ; Tomás et al., 2011 ).…”
Section: Resultsmentioning
confidence: 96%
“…Nevertheless, although immature, this somitic territory holds interesting molecular similarities with the bone tissue. Likewise, signaling reported for their instructive role during the bone metastatic process like CXCL12/SDF-1, WNT, and HGF, as well as extracellular matrix components like tenascin-C or fibronectins, are also present in the developing somitic domain ( Clézardin et al., 2021 ; Graf et al., 2021 ; Kar et al., 2020 ; Previdi et al., 2010 ; Scaal et al., 1999 ; Stebler et al., 2004 ; Tomás et al., 2011 ). This likely contributes to define the behaviors of grafted tumoral cells.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, fibril‐forming collagens are characterized by a large extracellular fiber with a continuous triple helix structure of about 300 nm, and a large peptide chain as long as 1000 amino acids. Previous studies have demonstrated that fibril‐forming collagens, such as type I/III/XI collagens, can promote tumor progression and serve as prognostic markers 9‐12 …”
Section: Introductionmentioning
confidence: 99%